Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Firm Value Yang Dimoderasi Oleh Harga Saham Pada Perusahaan Sektor Transportasi Dan Logistik Periode 2019-2023 - julianti, reina (Universitas Gorontalo, 2025)
This study aims to determine the effect of current ratio and debt to equity ratio on firm value moderated by stock prices in transportation and logistics sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The sample selection used purposive sampling technique and 19 company samples were selected from 37 populations of transportation and logistics sector companies. The data collection technique used is secondary data with data analysis techniques using panel data regression analysis with Eviews 10 software and the best model is obtained, namely the fixed effect model (FEM). Based on the results of this study, it shows that the current ratio and debt to equity ratio partially have a positive effect on firm value. Simultaneously, current ratio and debt to equity ratio affect firm value. Then, stock prices can moderate the relationship between current ratio and firm value. In addition, stock prices cannot moderate the relationship between debt to equity ratio and firm value.